National history and the world of nations capital, state, and the rhetoric of history in Japan, France, and the United States - Hill, Christopher L. (Durham Duke University Press, 2008)
Focusing on Japan, France, and the United States, Christopher L. Hill reveals how the writing of national history in the late nineteenth century made the reshaping of the world by capitalism and the nation-state seem natural and inevitable. The three countries, occupying widely different positions in the world, faced similar ideological challenges stemming from the rapidly changing geopolitical order and from domestic political upheavals: the Meiji Restoration in Japan, the Civil War in the United States, and the establishment of the Third Republic in France. Through analysis that is both comparative and transnational, Hill shows that the representations of national history that emerged in response to these changes reflected rhetorical and narrative strategies shared across the globe.
Includes bibliographical references (p. [283]-328) and index.
Keywords: Nationalism and historiography--Japan.